Literature Review: Analisa Konsep, Kebijakan dan Research Evidance dengan Masalah Napza di Masyarakat - Aeni, Nurul (Mando Care Jurnal, 2024)
Narcotics, alcohol, psychotropic substances and other addictive substances (NAPZA) are psychoactive substances that have the potential to change a person's behavior, feelings and thoughts. Drug abuse is a serious problem in Indonesia and the world. Various efforts have been made to tackle drug abuse, but there is still an increase in cases of abuse in several areas. This study aims to analyze the effectiveness of the Therapeutic Community (TC) method in social rehabilitation of drug abusers based on concepts, research evidence and government policies. The research method uses literature review from the Pubmed and Google Scholar databases with relevant keywords. Inclusion criteria include research between 2014 and 2022 in Indonesian or English. The research results show that the TC method is effective in reducing the level of drug abuse and the resulting antisocial behavior. TC programs involve interactions between members to support each other and influence positive behavior. However, the drop out rate is still a major challenge in implementing the TC program. Social rehabilitation of drug abusers is also carried out through medical and social approaches. The government has established a policy not to criminalize victims of drug abuse, but directs them to report themselves to Institutions Receiving Compulsory Reports (IPWL) to receive rehabilitation. In conclusion, the TC program is an effective approach in the social rehabilitation of drug abusers, although there are still challenges in its implementation. The importance of human resource support and public awareness in tackling drug abuse is the main focus in prevention and rehabilitation efforts.